Pathways to eating disorder care: A European multicenter study - Monteleone, Alessio Maria; Barone, Eugenia; Cascino, Giammarco; Schmidt, Ulrike; Gorwood, Philip; Volpe, Umberto; Abbate-Daga, Giovanni; Castellini, Giovanni; Díaz Marsá, Marina; Favaro, Angela; Fukutomi, Akira; Guillaume, Sebastien; et al. (European psychiatry, 2023)
BACKGROUND: The aim of this study was to assess barriers and facilitators in the pathways toward specialist care for eating disorders (EDs). METHODS: Eleven ED services located in seven European countries recruited patients with an ED. Clinicians administered an adapted version of the World Health Organization "Encounter Form," a standardized tool to assess the pathways to care. The unadjusted overall time needed to access the ED unit was described using the Kaplan-Meier curve. RESULTS: Four-hundred-nine patients were recruited. The median time between the onset of the current ED episode and the access to a specialized ED care was 2 years. Most of the participants did not directly access the specialist ED unit: primary "points of access" to care were mental health professionals and general practitioners. The involvement of different health professionals in the pathway, seeking help for general psychiatric symptoms, and lack of support from family members were associated with delayed access to ED units. CONCLUSIONS: Educational programs aiming to promote early diagnosis and treatment for EDs should pay particular attention to general practitioners, in addition to mental health professionals, and family members to increase awareness of these illnesses and of their treatment initiation process.
Keywords: Family; Health Personnel; poruchy příjmu potravy; educational; lidé; Europe; Feeding and Eating Disorders; eating disorders; Evropa; rodina; Barriers; health care policy; pathways to care; zdravotnický personál; Humans